IMPLEMENTASI METODE KETELADANAN UNTUK PENANAMAN AKHLAK PESERTA DIDIK DI MTS KALIPUCANG PANGANDARAN - Uus Hermansyah (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2019)
This research is conducted by background of influence of factors causing moral contamination which make the students have bad character or bad, among others bad behavior of parent or close family, bad behavior of friend, negative impact of information from mass media. The research method used is descriptive method is a method that attempts to describe something systematically, factually and accurately about various factors and the relationship between the phenomena investigated. Data analysis with the following steps: data selection, data classification, data interpretation, and draw conclusions. The conclusions of this research are: planning applied in the effort of implementation of exemplary method for cultivating morals of learners include: determination of program type; determination of program objectives, preparatory measures; organizing that is applied in the effort of implementation of exemplary method for cultivating morals learners to consider factors: human resources (manpower), carrying capacity, facilities owned, learning facilities, the source of funds and the source of funds; Implementation applied in effort implementation of exemplary method for cultivating morals of learners include: deliberate example; and unintentional examples; evaluation applied in effort implementation of exemplary method for cultivation morals learners consider: purpose of program expected or achieved results, learning activities, the form of evaluation and follow-up undertaken, the amount of budget absorption used.